IBV QX affects the antigen presentation function of BMDCs through nonstructural protein16 - Yaotang Wu; Yuchen Li; Jinhao Zhao; Yang Wu; Danqing Lu; Junpeng Jia; Tianxin Chen; Mingzhe He; Jian Lin; Qian Yang (Poultry Science, 2023)
ABSTRACT: The gamma-coronavirus infectious bronchitis virus (IBV) has a high mutation rate and mainly invades the respiratory mucosa, making it difficult to prevent and causing great economic losses. Nonstructural protein 16 (NSP16) of IBV QX also not only plays an indispensable role in virus invading but also might hugely influence the antigen's recognition and presentation ability of host BMDCs. Hence, our study tries to illustrate the underline mechanism of how NSP16 influences the immune function of BMDCs. Initially, we found that NSP16 of the QX strain significantly inhibited the antigen presentation ability and immune response of mouse BMDCs, which was stimulated by Poly (I:C) or AIV RNA. Besides mouse BMDCs, we also found that NSP16 of the QX strain also significantly stimulated the chicken BMDCs to activate the interferon signaling pathway. Furthermore, we preliminarily demonstrated that IBV QX NSP16 inhibits the antiviral system by affecting the antigen-presenting function of BMDCs.